Sodium ion battery hard carbon negative electrode material, preparation method thereof, negative electrode and sodium ion battery

By calcining hard carbon materials at low temperatures and forming a sodium polyphosphate coating layer in situ, the problem of poor interfacial dynamics of hard carbon anode materials in sodium-ion batteries was solved, achieving high initial efficiency and excellent cycle stability, thus improving the overall performance of sodium-ion batteries.

CN121020557BActive Publication Date: 2026-01-23NANKAI UNIV +1
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202511524770.0
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2025-10-24
Publication Date
2026-01-23
Estimated Expiration
2045-10-24

AI Technical Summary

Technical Problem

Existing hard carbon anode materials in sodium-ion batteries suffer from poor interfacial kinetics, low first-cycle coulombic efficiency, and poor cycle stability, mainly due to the low diffusion rate of sodium ions in the disordered structure of hard carbon and frequent side reactions in the electrolyte.

Method used

Hard carbon materials are calcined at low temperatures to eliminate unsaturated oxygen-containing sites and form a sodium polyphosphate coating layer in situ. Low-temperature calcination eliminates defect sites on the surface of hard carbon, promotes sodium ion diffusion, and inhibits interfacial side reactions. A mixture of phosphorus and sodium sources is used to form a sodium polyphosphate coating layer on the surface of hard carbon, thereby improving interfacial stability.

Benefits of technology

It significantly improves the first-cycle coulombic efficiency and cycle stability of hard carbon anode materials, enhances the rate performance of sodium-ion batteries, achieves an initial efficiency of 89.4%, retains more than 90% of the capacity after 200 cycles, and reduces irreversible capacity loss.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN121020557B_ABST
    Figure CN121020557B_ABST
Patent Text Reader

Abstract

The application belongs to the technical field of battery material synthesis, and discloses a sodium-ion battery hard carbon negative electrode material and a preparation method, a negative electrode and a sodium-ion battery. The method uniformly mixes the hard carbon negative electrode material and a sodium polyphosphate precursor material composed of a sodium source and a phosphorus source, and eliminates the unsaturated oxygen-containing sites of the hard carbon material under low-temperature (500-700 DEG C) calcination to reduce the first-cycle irreversible capacity loss. Meanwhile, an in-situ formed sodium polyphosphate coating layer improves the sodium ion diffusion rate. The method realizes the surface modification and coating of the hard carbon material in one step, the obtained hard carbon negative electrode material has a first-week coulomb efficiency of >89.4%, a 200 mA·g ‑1 cycle capacity retention rate of >90%, and excellent rate performance. The application has simple and controllable process, low raw material cost and environmental friendliness, and is suitable for large-scale production.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of battery material synthesis technology, specifically relating to a hard carbon anode material for sodium-ion batteries and its preparation method, the anode, and the sodium-ion battery. Background Technology

[0002] Sodium-ion batteries are considered a promising energy storage technology due to their abundant resources, low cost, and similar operating principle to lithium-ion batteries. Hard carbon anodes are considered ideal for sodium-ion batteries due to their high specific capacity, low operating potential, and long cycle life. The interfacial kinetics of hard carbon anodes are closely related to the chemical properties of the electrolyte. The sodium ion radius (1.02 Å) is larger than that of lithium ions (0.76 Å), and the strong Coulomb interaction between the highly polar carbonyl groups in commercial carbonate solvents and sodium ions significantly increases the desolvation energy barrier of sodium ions at the hard carbon interface, leading to a reduced diffusion rate of sodium ions in the disordered structure of hard carbon. In addition, surface defects on hard carbon accelerate electrolyte reduction, generating a solid electrolyte interphase (SEI) film rich in organic components. During cycling, the SEI film undergoes repeated rupture and regeneration due to mechanical stress or chemical instability. This dynamic process continuously consumes active sodium ions and electrolyte, resulting in low initial coulombic efficiency (typically <80%) and accelerated capacity decay during cycling. Therefore, regulating and optimizing the interface structure of hard carbon anodes to improve interface dynamics and suppress side reactions is the key to breaking through the performance bottleneck of sodium-ion batteries and improving their cycle stability.

[0003] Currently, modifying the hard carbon anode material itself or its surface is an effective way to improve interfacial stability.

[0004] (1) Surface coating: Constructing a uniform, ultrathin inert or fast ion conductor protective layer on the surface of hard carbon (such as preparing alumina by atomic layer deposition) can physically isolate the direct contact between the electrolyte and the active surface, reduce side reactions and improve interface stability.

[0005] (2) Element doping: Introducing heteroatoms (such as nitrogen doping) into the hard carbon framework can regulate the surface electronic structure and chemical properties, and reduce the adsorption / desorption energy barrier of sodium ions on the surface.

[0006] (3) Structural regulation: Optimizing the pore structure and surface morphology of hard carbon (such as designing vertical channels) can shorten the diffusion path of sodium ions and increase the active surface area, thereby improving the reaction kinetics.

[0007] The aforementioned technologies still have limitations such as complex processes, potential pore blockage, high precursor toxicity, and unstable effects. Summary of the Invention

[0008] To overcome the shortcomings of existing technologies, this invention provides a hard carbon anode material for sodium-ion batteries, its preparation method, the anode material, and the sodium-ion battery. Calcination at low temperatures (500-700℃) eliminates unsaturated oxygen-containing sites in the hard carbon material, reducing irreversible capacity loss in the first cycle. Simultaneously, an in-situ sodium polyphosphate coating layer is formed to enhance the sodium-ion diffusion rate and suppress interfacial side reactions. The prepared hard carbon anode material for sodium-ion batteries exhibits excellent rate performance, high first-cycle coulombic efficiency, high cycle stability, and good versatility.

[0009] This invention can be achieved through the following technical solutions:

[0010] The first aspect of this invention discloses a method for preparing a high-rate, high-efficiency hard carbon anode material for sodium-ion batteries, comprising the following steps:

[0011] (1) Phenol and formaldehyde are mixed in ethanol, stirred at 50-70℃, filtered and dried to obtain a phenolic resin precursor, which is then subjected to an inert atmosphere at 5-15℃·min. -1 The temperature is increased to 1200-1400℃ at a heating rate, and then carbonized at that temperature for 2-4 hours to obtain hard carbon material.

[0012] (2) The hard carbon material is uniformly mixed with the sodium polyphosphate precursor and dried to obtain a mixture, wherein the sodium polyphosphate precursor is composed of a sodium source and a phosphorus source;

[0013] (3) The mixture is calcined in an inert atmosphere to eliminate unsaturated oxygen-containing sites on the surface of hard carbon and form a sodium polyphosphate coating layer in situ, thereby obtaining a high-rate, high-efficiency sodium-ion battery hard carbon anode material.

[0014] In this invention, the phosphorus source transforms into sodium phosphate and sodium metaphosphate structures during low-temperature calcination (500-700℃), while the sodium source assists in the formation of pure-phase sodium phosphate. Unsaturated oxygen-containing functional groups and defect sites in the hard carbon further catalyze the condensation of sodium phosphate to form long-chain sodium polyphosphate. The modification layer formed by sodium polyphosphate on the surface of the hard carbon material provides a three-dimensional diffusion channel for sodium ions, promoting sodium ion transport at the hard carbon / electrolyte interface, alleviating sodium ion enrichment on the hard carbon material surface, and inhibiting sodium precipitation. Furthermore, the sodium polyphosphate coating layer can inhibit the decomposition of organic solvents in the electrolyte and form an inorganic-rich SEI film.

[0015] This improves the fast-charging capability, rate performance, and cycle performance of hard carbon materials. On the other hand, when sodium phosphate reacts with unsaturated oxygen-containing sites in hard carbon during low-temperature calcination to form sodium polyphosphate, it reduces the defect degree of hard carbon and the irreversible sodium ion loss caused by the formation of the SEI film during the first charge and discharge cycle, thereby improving the first-cycle coulombic efficiency and cycle stability of hard carbon anode materials.

[0016] Further, the sodium source is one or at least two of sodium carbonate, sodium bicarbonate, sodium hydroxide, and sodium acetate; the phosphorus source is one or at least two of sodium dihydrogen phosphate, disodium hydrogen phosphate, ammonium phosphate, ammonium dihydrogen phosphate, and phosphoric acid. More preferably, the sodium source is sodium carbonate and the phosphorus source is sodium dihydrogen phosphate. This synthesis process is mild, has fewer impurities, and uses inexpensive raw materials.

[0017] Furthermore, the mixing method employs wet ball milling at a speed of 300-500 rpm for 2-4 hours. The grinding aid in wet ball milling is water or ethanol, which is more conducive to material mixing under wet conditions.

[0018] Further, the mass ratio of the sodium source, phosphorus source, and hard carbon material is 0.02-0.08:0.02-0.07:1. More preferably, the mass ratio of the sodium source, phosphorus source, and hard carbon material is 0.04:0.03:1. When the content of phosphorus source and sodium source is too low, it is insufficient to suppress the side reactions at the hard carbon interface and has limited effect on improving battery performance; while when the content of phosphorus source and sodium source is too high, the excess sodium phosphate cannot be effectively stored, which will reduce the energy density of the battery.

[0019] Furthermore, the calcination temperature is 500-700℃, the calcination atmosphere is nitrogen or argon, the calcination time is 4-9 hours, and the gas flow rate is 50-200 mL / min. Excessive temperature will cause the hard carbon structure to collapse, affecting the sodium storage capacity; excessively low temperature will prevent the sodium and phosphorus source precursors from forming pure-phase sodium polyphosphate.

[0020] Furthermore, resin-based hard carbon, biomass and its derivatives hard carbon, polymer-based hard carbon, and coal-based hard carbon materials are all applicable to this method. The resin-based hard carbon is one of phenolic resin, epoxy resin, and polyfurfuryl alcohol resin; the biomass and its derivatives hard carbon is one of coconut shell, rice husk, bamboo, cellulose, lignin, and starch; the polymer-based hard carbon is polyacrylonitrile or polyimide; and the coal-based hard carbon is anthracite or lignite.

[0021] The second aspect of this invention discloses a high-rate, high-efficiency sodium-ion battery hard carbon anode material prepared by the method described above.

[0022] The third aspect of this invention discloses a sodium-ion battery anode prepared from the aforementioned high-rate, high-efficiency sodium-ion battery hard carbon anode material.

[0023] Furthermore, the preparation method is as follows: the high-rate, high-efficiency sodium-ion battery hard carbon anode material, conductive carbon black, and binder sodium carboxymethyl cellulose are mixed evenly in a mass ratio of 8:1:1, an appropriate amount of deionized water dispersant is added to make a slurry, and then the slurry is uniformly coated on an aluminum foil current collector. The slurry is dried in a vacuum environment at 75-85℃ for 9-12 hours to obtain the sodium-ion battery anode.

[0024] The fourth aspect of the present invention discloses a sodium-ion battery, which is obtained by sequentially assembling the high-rate, high-efficiency sodium-ion battery negative electrode, separator, electrolyte and positive electrode in an argon atmosphere.

[0025] Furthermore, the diaphragm is made of glass fiber; the solute in the electrolyte is 1M sodium hexafluorophosphate, the solvent is ethylene carbonate, ethyl methyl carbonate, and dimethyl carbonate in a volume ratio of 1:1:1, and the positive electrode active material is a sheet of metallic sodium.

[0026] This invention significantly improves the first-cycle efficiency, rate capability, and cycle performance of hard carbon anode materials by calcining hard carbon, sodium source, and phosphorus source at low temperature to eliminate defect sites on the surface of hard carbon and constructing a sodium polyphosphate coating layer in situ on the surface of hard carbon. Its mechanism of action includes: (1) physically isolating the direct contact between the electrolyte and hard carbon, and suppressing the side reaction of electrolyte solvent decomposition at the hard carbon interface; (2) promoting the full decomposition of anions in the electrolyte and inducing the formation of a stable SEI film of inorganic components rich in sodium fluoride and sodium phosphate; (3) fast-ion conductive sodium polyphosphate accelerates the diffusion of sodium ions on the surface of hard carbon and reduces the charge transfer resistance of sodium ions; (4) sodium source and phosphorus source condense with defect sites on the surface of hard carbon during low-temperature calcination to form sodium polyphosphate, reducing irreversible sodium loss caused by the formation of SEI film during the first discharge cycle.

[0027] Advantages and beneficial effects of the present invention:

[0028] (1) This invention uses low-temperature calcination of sodium source, phosphorus source, and hard carbon material to eliminate unsaturated oxygen-containing sites in the hard carbon material and reduce irreversible capacity loss in the first cycle; at the same time, a sodium polyphosphate (instead of pre-existing sodium phosphate) coating layer is formed in situ on the surface of the hard carbon. This method achieves surface modification and coating of hard carbon material in one step, and the resulting hard carbon anode material achieves an initial efficiency of 89.4% (an improvement of 8.2 percentage points compared to the original hard carbon), at 200 mA·g -1 The capacity retention rate is >90% after 200 cycles, and the rate performance is significantly improved, which is something that existing technology (direct mixing of sodium phosphate) cannot achieve.

[0029] (2) The raw materials used in this invention are inexpensive and environmentally compatible. The process is simple and controllable, and the method is universal. The hard carbon anode material prepared meets the performance requirements of commercial sodium-ion batteries and has the potential for large-scale application. Attached Figure Description

[0030] Figure 1 The image shows the XRD pattern of the original hard carbon material in Comparative Example 1.

[0031] Figure 2 TEM image of the original hard carbon material in Comparative Example 1;

[0032] Figure 3The image shows the XRD pattern of the hard carbon anode material for sodium-ion batteries obtained in Example 1.

[0033] Figure 4 This is a TEM image of the hard carbon anode material for sodium-ion batteries obtained in Example 1;

[0034] Figure 5 The image shows a TEM image of the hard carbon anode material for sodium-ion batteries obtained in Comparative Example 4.

[0035] Figure 6 The first charge-discharge curve of the sodium-ion battery prepared from the original hard carbon material in Comparative Example 1 is shown. (Active material loading: 3 mg / cm³) 2 Current density: 20 mA·g -1 Voltage window: 0.01 - 1.5V;

[0036] Figure 7 The image shows the first charge-discharge curve of a sodium-ion battery prepared using the hard carbon anode material obtained in Example 1. (Active material loading: 3 mg / cm³) 2 Current density: 20 mA·g -1 Voltage window: 0.01 - 1.5V;

[0037] Figure 8 Comparison of rate performance of sodium-ion batteries prepared with hard carbon materials in Examples 1, 2, 1, and 2. (Active material loading: 3 mg / cm³) 2 Voltage window: 0.01 - 1.5V;

[0038] Figure 9 Cycle performance test graphs of sodium-ion batteries prepared with hard carbon materials in Examples 1, 2, Comparative Examples 1 and 2. (Active material loading: 3 mg / cm³) 2 Current density: 200 mA·g -1 Voltage window: 0.01 - 1.5V. Detailed Implementation

[0039] The present invention will be further described in detail below through specific embodiments. The following embodiments are merely descriptive and not limiting, and should not be used to limit the scope of protection of the present invention.

[0040] Unless otherwise specified, the phenol, formaldehyde, ethanol, sodium carbonate, ammonium dihydrogen phosphate, and other reagents used in the examples are all commercially available or obtained through conventional synthesis methods in the art.

[0041] Comparative Example 1

[0042] Phenol (100 g), formaldehyde (70 mL), and ethanol (800 mL) were placed in a three-necked flask equipped with a reflux condenser and a mechanical stirrer. The resulting mixture was reacted at 60 °C with continuous stirring for 8 hours to produce phenolic resin. The filtered and dried precursor was carbonized in a vacuum tube furnace at 1300 °C for 3 hours under argon atmosphere at a heating rate of 10 °C / min. -1 This yields the original hard carbon material.

[0043] The XRD pattern of the original hard carbon material is as follows: Figure 1 As shown in the figure, the original hard carbon material exhibits typical hard carbon structural characteristic peaks and contains no impurity phases. Its TEM image is shown below. Figure 2 As shown in the figure, the surface of the original hard carbon material exhibits a relatively small number of disordered short-range microcrystalline graphite regions.

[0044] Example 1

[0045] The original hard carbon material obtained from Comparative Example 1, sodium carbonate, and ammonium dihydrogen phosphate were placed in a ball mill jar at a mass ratio of 93.5:3.4:3.1. An appropriate amount of ethanol solvent was added, and the mixture was wet-milled in a vertical ball mill at 400 rpm for 3 hours. After drying and grinding, the mixture was transferred to an alumina crucible and calcined at 600°C for 5 hours in a vacuum tube furnace under argon atmosphere to obtain sodium polyphosphate-coated sodium-ion battery hard carbon anode material.

[0046] The XRD pattern of the sodium-ion battery hard carbon anode material obtained in Example 1 is shown below. Figure 3 As shown in the figure, the sodium-ion battery hard carbon anode material coated with sodium polyphosphate still retains the phase structure of hard carbon materials, while also displaying the characteristic peaks of sodium polyphosphate. Its TEM image is shown below. Figure 4 As shown in the figure, the surface of the coated hard carbon material has a rich short-range microcrystalline graphite region structure, which is conducive to the rapid insertion and extraction of sodium ions.

[0047] Example 2

[0048] The difference from Example 1 is that the original hard carbon material, sodium carbonate and ammonium dihydrogen phosphate are mixed in a mass ratio of 92.6:3.2:4.2 to obtain sodium polyphosphate-coated sodium-ion battery hard carbon anode material.

[0049] Example 3

[0050] The difference from Example 1 is that the reaction was carried out in a vacuum tube furnace under argon atmosphere at 500°C for 5 hours to obtain sodium-ion battery hard carbon anode material coated with sodium polyphosphate.

[0051] Comparative Example 2

[0052] The difference from Example 1 is that it does not contain a sodium source. The preparation method is as follows: the original hard carbon material and ammonium dihydrogen phosphate are mixed at a mass ratio of 93.5:6.5, and the other experimental conditions are kept unchanged.

[0053] Comparative Example 3

[0054] The difference from Example 1 is that it does not contain a phosphorus source. The preparation method is as follows: the original hard carbon material and sodium carbonate are mixed at a mass ratio of 93.5:6.5, and the other experimental conditions are kept unchanged.

[0055] Comparative Example 4

[0056] The difference from Example 1 is that the original hard carbon material of Comparative Example 1 was mixed with ready-made or pre-synthesized sodium phosphate (instead of the precursor) in the same proportion and treated under the same inert atmosphere and low temperature calcination conditions.

[0057] TEM image of the hard carbon anode material for sodium-ion batteries in Comparative Example 4 is shown below. Figure 5 As shown in the figure, the hard carbon material exhibits a disordered structure and a small amount of short-range microcrystalline graphite regions.

[0058] Test methods

[0059] Preparation of sodium-ion battery anode: Raw hard carbon material or sodium polyphosphate-coated sodium-ion battery hard carbon anode material, conductive carbon black, and sodium carboxymethyl cellulose binder are mixed uniformly at a mass ratio of 8:1:1. An appropriate amount of deionized water dispersant is added to prepare a slurry. The slurry is uniformly coated onto an aluminum foil current collector and dried under vacuum at 80°C for 10 hours to obtain the sodium-ion battery anode. The sodium-ion battery anode is then cut into 12 mm diameter discs for battery assembly.

[0060] Sodium-ion battery preparation: The sodium-ion battery negative electrode, separator, electrolyte and positive electrode are assembled sequentially in an argon atmosphere to finally obtain a sodium-ion battery; the separator is glass fiber; the solute in the electrolyte is 1M sodium hexafluoropolyphosphate, the solvent is ethylene carbonate, ethyl methyl carbonate and dimethyl carbonate in a volume ratio of 1:1:1, and the positive electrode active material is metallic sodium sheet.

[0061] Sodium-ion batteries prepared using the hard carbon anode materials in the examples and comparative examples were tested at a temperature of 25°C and a voltage range of 0.01–1.5 V, at a concentration of 20 mA·g. -1 The first-cycle coulombic efficiency was obtained by testing the first-cycle charge-discharge curves at a current density of 200 mA·g. -1 Cyclic stability tests were performed at current density to obtain the capacity retention after 200 cycles; at 50 mA·g -1 100 mA·g -1 200 mA·g -1500 mA·g -1 The rate performance of the sodium-ion batteries was tested separately. The electrochemical performance test results are shown in Table 1.

[0062] Table 1 Electrochemical performance of sodium-ion batteries

[0063]

[0064] Figure 6 This is the first charge-discharge curve of the sodium-ion battery prepared with the original hard carbon material in Comparative Example 1. Combined with the electrochemical performance of the sodium-ion battery in Table 1, the original hard carbon material at 20 mA·g... -1 When tested at current density, the first-cycle discharge specific capacity was 302.1 mAh·g. -1 In the first week, Cullen's efficiency was only 81.2%.

[0065] Figure 7 This is a charge-discharge curve of a sodium-ion battery prepared with the hard carbon anode material in Example 1. The curve shows that at 20 mA·g... -1 Testing at current density showed that the first-cycle discharge specific capacity of Example 1 was similar to that of the original hard carbon material, but the first-cycle coulombic efficiency was 89.4%, a significant improvement compared to the original hard carbon material. This is mainly because sodium carbonate and ammonium dihydrogen phosphate react with unsaturated oxygen-containing sites on the surface of the original hard carbon material during calcination at 600°C to generate sodium phosphate, thereby reducing irreversible sodium loss caused by the SEI film formed during the first-cycle discharge.

[0066] Figure 8 This graph shows a comparison of the rate performance of sodium-ion batteries prepared with hard carbon materials in Examples 1, 2, 1, and 2. As can be seen from the graph, Examples 1 and 2 show the best rate performance at 100 mA·g. -1 200 mA·g -1 500 mA·g -1 The capacity performance of the materials was higher than that of Comparative Example 1, indicating its excellent rate performance. At the same time, the data in Table 1 show that when hard carbon is modified with sodium carbonate (Comparative Example 3) or ammonium dihydrogen phosphate (Comparative Example 2) alone, its rate performance is similar to that of the original hard carbon material.

[0067] Figure 9The graph shows a comparison of the cycle performance of sodium-ion batteries prepared from hard carbon materials in Examples 1, 2, 1, and 2. The graphs show that the cycle stability of Examples 1 and 2 is superior to that of Comparative Examples 1 and 2, with a capacity retention rate exceeding 90% after 200 cycles. This indicates that sodium polyphosphate synthesized by low-temperature calcination of the precursor can significantly improve the initial efficiency, rate capability, and cycle stability. Combined with the data in Table 1, Comparative Example 4 shows that directly mixing and calcining ready-made or pre-synthesized sodium phosphate with the original hard carbon material to prepare the hard carbon anode material for sodium-ion batteries, while improving the rate capability and cycle stability to some extent, cannot achieve the same effect as the examples. This indicates that low-temperature calcination of the sodium source, phosphorus source, and original hard carbon material mixture eliminates defect sites on the hard carbon surface while simultaneously forming a uniformly thick sodium polyphosphate coating layer on the surface of the original hard carbon material, significantly improving the initial efficiency, rate capability, and cycle performance of the hard carbon anode material.

[0068] The above description is only a preferred embodiment of the present invention. It should be noted that for those skilled in the art, several modifications and improvements can be made without departing from the inventive concept, and these all fall within the protection scope of the present invention.

Claims

1. A method for preparing a high-rate, high-efficiency hard carbon anode material for sodium-ion batteries, characterized in that, Includes the following steps: (1) Phenol and formaldehyde are mixed in ethanol, stirred at 50-70℃, filtered and dried to obtain a phenolic resin precursor, which is then subjected to an inert atmosphere at 5-15℃·min. -1 The temperature is increased to 1200-1400℃ at a heating rate, and then carbonized at that temperature for 2-4 hours to obtain hard carbon material. (2) The hard carbon material is uniformly mixed with the sodium polyphosphate precursor and dried to obtain a mixture, wherein the sodium polyphosphate precursor is composed of a sodium source and a phosphorus source; (3) The mixture is calcined in an inert atmosphere to eliminate unsaturated oxygen-containing sites on the surface of hard carbon and form a sodium polyphosphate coating layer in situ, thereby obtaining a high-rate, high-efficiency sodium-ion battery hard carbon anode material.

2. The preparation method according to claim 1, characterized in that, The sodium source is one or at least two of sodium carbonate, sodium bicarbonate, sodium hydroxide, and sodium acetate; the phosphorus source is one or at least two of sodium dihydrogen phosphate, disodium hydrogen phosphate, ammonium phosphate, ammonium dihydrogen phosphate, and phosphoric acid.

3. The preparation method according to claim 1, characterized in that, The mixing method uses wet ball milling at a speed of 300-500 rpm for 2-4 hours.

4. The preparation method according to claim 1, characterized in that, The mass ratio of the sodium source, phosphorus source and hard carbon material is 0.02-0.08:0.02-0.07:

1.

5. The preparation method according to claim 1, characterized in that, The calcination temperature is 500-700℃, the calcination atmosphere is nitrogen or argon, and the calcination time is 4-9 hours.

6. A high-rate, high-efficiency sodium-ion battery hard carbon anode material prepared by the preparation method according to any one of claims 1-5.

7. A sodium-ion battery anode prepared from the high-rate, high-efficiency sodium-ion battery hard carbon anode material as described in claim 6.

8. The sodium-ion battery negative electrode according to claim 7, characterized in that, The preparation method is as follows: the high-rate, high-efficiency sodium-ion battery hard carbon anode material, conductive carbon black, and binder sodium carboxymethyl cellulose are mixed evenly in a mass ratio of 8:1:

1. An appropriate amount of deionized water dispersant is added to make a slurry, which is then uniformly coated onto an aluminum foil current collector. The slurry is dried in a vacuum environment at 75-85℃ for 9-12 hours to obtain the sodium-ion battery anode.

9. A sodium-ion battery, characterized in that, It is obtained by assembling the sodium-ion battery negative electrode, separator, electrolyte and positive electrode as described in claim 7 in an argon atmosphere. The active material of the positive electrode is a metallic sodium sheet, the solute in the electrolyte is 1M sodium hexafluorophosphate, and the solvent is ethylene carbonate, ethyl methyl carbonate and dimethyl carbonate in a volume ratio of 1:1:1.

Citation Information

Patent Citations

  • Method for in-situ preparation of porous silicon-carbon composite negative electrode material

    CN111646472A

  • Modified hard carbon material, preparation method thereof and application of modified hard carbon material in sodium-ion battery

    CN119725452A